Enhanced thermal and electrochemical properties in La0.8Sr0.2MnO3-δ-Pr6O11 nanocomposite cathodes for solid oxide fuel cells - Zamudio-García, Javier; Caizán-Juanarena, Leire; Dos-Santos-Gómez, Lucía; Porras-Vázquez, José Manuel; Ramírez-Losilla, Enrique; Marrero-López, David (Elsevier, 2025)
La0.8Sr0.2MnO3-δ (LSM)-Pr6O11 nanocomposite electrodes are prepared via a one-step spray-pyrolysis deposition directly onto the electrolyte and evaluated as cathodes for solid oxide fuel cells (SOFCs). The nanoscale integration of two immiscible phases effectively inhibits grain growth while improving mechanical compatibility with the electrolyte. The confinement of the fluorite Pr6O11 phase at the nanoscale during the self-assembly process, achieved by adding the perovskite-type LSM phase with a different crystal structure, hinder the thermally induced phase transitions of Pr6O11 compared to the bulk material. The extended triple-phase-boundary (TPB) in these nanoengineered electrodes leads to exceptional electrochemical performance, achieving a polarization resistance of 0.21 Ω cm2 at 650 °C, significantly lower than the 5.8 Ω cm2 measured for a traditional screen-printed LSM cathode. An anode-supported cell incorporating these nanocomposite electrodes achieves a peak power density of 1.22 W cm−2 at 800 °C in wet H2, far exceeding the 0.58 W cm−2 observed for the single cell with a commercial LSM electrode under identical conditions. These findings underscore the significant benefits of advanced nanostructured electrode designs and innovative fabrication techniques in achieving high performance and durability in SOFCs.
Keywords: Cristalografía; Cátodos; Pilas de combustible; SOFC; La0.8Sr0.2MnO3-δ; Pr6O11; Nanocomposite; Cathode; Electrode design